Diamond Nanowires: A Novel Platform for Electrochemistry and Matrix-Free Mass Spectrometry - Sabine Szunerits; Yannick Coffinier; Rabah Boukherroub (Sensors, 2015)
Over the last decades, carbon-based nanostructures have generated a huge interest from both fundamental and technological viewpoints owing to their physicochemical characteristics, markedly different from their corresponding bulk states. Among these nanostructured materials, carbon nanotubes (CNTs), and more recently graphene and its derivatives, hold a central position. The large amount of work devoted to these materials is driven not only by their unique mechanical and electrical properties, but also by the advances made in synthetic methods to produce these materials in large quantities with reasonably controllable morphologies. While much less studied than CNTs and graphene, diamond nanowires, the diamond analogue of CNTs, hold promise for several important applications. Diamond nanowires display several advantages such as chemical inertness, high mechanical strength, high thermal and electrical conductivity, together with proven biocompatibility and existence of various strategies to functionalize their surface. The unique physicochemical properties of diamond nanowires have generated wide interest for their use as fillers in nanocomposites, as light detectors and emitters, as substrates for nanoelectronic devices, as tips for scanning probe microscopy as well as for sensing applications. In the past few years, studies on boron-doped diamond nanowires (BDD NWs) focused on increasing their electrochemical active surface area to achieve higher sensitivity and selectivity compared to planar diamond interfaces. The first part of the present review article will cover the promising applications of BDD NWS for label-free sensing. Then, the potential use of diamond nanowires as inorganic substrates for matrix-free laser desorption/ionization mass spectrometry, a powerful label-free approach for quantification and identification of small compounds, will be discussed.